Mean muscle activation comparison between fastballs and curveballs with respect to the upper and lower extremity. (20th September 2019) - Smidebush, Megan; Stewart, Ethan; Shapiro, Robert; Chander, Harish; Knight, Adam
Abstract: Baseball research on muscle activity (upper and lower extremity) during the throwing motion is important to understanding pitching mechanics for the future. Therefore, it is the purpose of this research study to compare the lower extremity muscle and upper extremity muscle activation patterns associated with the curveball pitch and the fastball pitch from the stretch position. Twelve skilled (NCAA collegiate level) pitchers volunteered to be in this study, with a mean age of 22.3 ± 4.53 years, mean height of 1.74 ± 0.13 m, and mean mass of 89.0 k ± 10.97 kg. The pitchers were fitted with six surface electromyography (EMG) bipolar electrodes on the stride leg biceps femoris, medial gastrocnemius, ipsilateral side lower trapezius, upper trapezius, triceps brachii and biceps brachii. Each pitcher underwent maximum voluntary isometric contraction (MVIC) testing and then performed the fastball & curveball pitching sequence. All EMG variables of interest were normalized using MVIC data and compared between pitching type. A repeated measures ANOVA was conducted for all muscle activity as well. If significance was found a pairwise analysis (Bonferroni) was performed between pitch type, using SPSS (p 0.05). Significant differences in the mean muscle activity for the fastball and curveball pitched from the stretch were observed. A higher level of muscle activity was found for the stretch fastball when compared to the stretch curveball. This study was able to provide a baseline measurement of muscle activity; however, kinematics and kinetics should be measured in future studies.